A mesoscale material and macroscale structure joint design for perforated caissons made with ultrahigh-performance concrete. (December 2022) - Jin, Zijian; Fang, Hui; Liu, Yong
Abstract: A mesoscale material and macroscale structure joint methodology, which can be utilized for the calculation and optimization of coastal structures designed with ultrahigh-performance concrete (UHPC), was presented. In the material-level analysis of UHPC, a three-dimensional representative volume element (RVE) model was developed to reveal the physical relations between the mesoscale characteristics (e.g., matrix and fibers) and material macroscale properties (e.g., constitutive model and yield criterion). To couple the material and structural analyses, a user-defined material mechanical behaviour subroutine (UMAT/VUMAT in ABAQUS) was developed, in which the mesoscale characteristics of the UHPC were introduced through the constitutive model's parameters. Finite element method (FEM) models containing multiscale (mesoscale material and macroscale structure) parameters were developed for calculating the load-carrying capacity of multiple types of perforated walls in a representative caisson. As an illustration, this meso -macro joint methodology was utilized to minimize the reinforcement ratio and the stress concentration in the perforated UHPC wall, which relied on the interaction of the parameters (e.g., fiber volume fraction and hole ratio) of meso -material and macro-structure. These results demonstrated the potential of multiscale joint design to achieve the physically significant optimization of a structure in coastal engineering.